Use of Magnetic Resonance Imaging in the Diagnosis of Takayasu's Arteritis During Pregnancy: A Case Report - Coel, Marc; Saito, Robert; Endo, Patti Murakami (American Journal of Perinatology, 1993)
We report a case of Takayasu's arteritis in a 29-year-old primigravid woman. The diagnosis of Takayasu's arteritis is usually made on the basis of clinical findings, with definitive diagnosis being made by angiography. To avoid the large amount of radiation needed for angiography, we used magnetic resonance imaging to establish a presumptive diagnosis. The diagnosis was confirmed two weeks postpartum by angiography.